Immunoinformatics Approach to Design a Multi-Epitope Vaccine against Cutaneous Leishmaniasis - Shumaila Naz; Aiman Aroosh; Ayse Caner; Esra Atalay Şahar; Seray Toz; Yusuf Ozbel; Sumra Wajid Abbasi (Vaccines, 2023)
Cutaneous Leishmaniasis (CL), a neglected vector-borne disease caused by protozoan parasite Leishmania major (L. major), is a major public health concern, and the development of new strategies to reduce the disease incidence has become a top priority. Advances in immunoinformatics and in-silico epitope prediction could be a promising approach to designing a finest vaccine candidate. In this study, we aimed to design a peptide-based vaccine against CL using computational tools and identified ten B-cell-derived T-cell epitopes from the glycoprotein gp63 of L. major. All of the potential immunodominant epitopes were used to design a vaccine construct along with a linker and an adjuvant at the N-terminal for enhancing its immunogenicity. Additionally, many characteristics of the proposed vaccine were examined, and it was confirmed to be non-allergenic, non-toxic, and thermally stable. To assess the vaccine interaction with the innate immune toll-like receptor-4 (TLR-4), a 3D structure of the vaccine construct was developed. Molecular docking and molecular dynamic simulation were used to confirm the binding and to assess the stability of the vaccine-TLR4 complex and interactions, respectively. In conclusion, our multi-epitope vaccine will provide a gateway to analyze the protein function of a potential vaccine candidate against CL.